Model-Level Integration of the OCL Standard Library Using a Pivot Model with Generics Support - Bräuer, Matthias; Demuth, Birgit (Electronic Communications of the EASST, 2007)
OCL 2.0 specifies a standard library of predefined types and associated operations. A model-level representation of the library is required to reference its elements within the abstract syntax model created by an OCL parser. Existing OCL engines build this model in the implementation code which severely limits reusability, flexibility and maintainability. To address these problems, we show how a common pivot model with explicit support for template types can help to externalize the definition of the standard library and integrate it with instances of arbitrary domain-specific modeling languages. We exemplify the feasibility of our approach with a prototypical implementation for the Dresden OCL2 Toolkit and present a tailored EMF editor for modeling the OCL types and operations. We limit our discussion to the model level, i.e., we do not consider an implementation of the standard library for an execution engine.